(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This research highlights the connections between culturally adept Wayúu women and the mathematical understanding intertwined in crafting their traditional Wayúu mochilas within their cultural milieu. Employing an ethnomathematical framework in tandem with qualitative methodologies encompassing ethnographic techniques, we used triangulated analytical frameworks established through semi-structured interviews. The study seeks to demonstrate the capacity to transmit ancestral and mathematical knowledge to younger generations, with the fundamental objective of upholding cultural heritage.